No Evidence for Passivation Effects of Na and K at Grain Boundaries in Polycrystalline Cu(In, Ga)Se2 Thin Films for Solar Cells. Issue 8 (12th June 2019) - Abou-Ras, Daniel; Nikolaeva, Aleksandra; Caicedo Dávila, Sebastián; Krause, Maximilian; Guthrey, Harvey; Al-Jassim, Mowafak; Morawski, Marcin; Scheer, Roland
Abstract : Thin‐film solar cells based on Cu(In, Ga)Se2 (CIGSe) absorber layers reach conversion efficiencies of above 20%. One key to this success is the incorporation of alkali metals, such as Na and K, into the surface and the volume of the CIGSe thin film. The present work discusses the impact of Na and K on the grain‐boundary (GB) properties in CIGSe thin films, i.e., on the barriers for charge carriers, Φb, and on the recombination velocities at the GBs, s GB . First, the physics connected with these two quantities as well as their impact on the device performance are revised, and then the values for the barrier heights and recombination velocities are provided from the literature. The s GB values are measured by means of a cathodoluminescence analysis of Na‐/K‐free CIGSe layers as well as on CIGSe layers on Mo/sapphire substrates, which are submitted to only NaF or only KF postdeposition treatments. Overall, passivating effects on GBs by neither Na nor K can be confirmed. The GB recombination velocities seem to remain on the same order of magnitude, in average about 10 3 –10 4 cm s −1, irrespective of whether CIGSe thin films are Na‐/K‐free or Na‐/K‐containing. Abstract : Alkali metals are reported to influence the device performance of Cu(In, Ga)Se2 (CIGSe) solar cells substantially. The present work shows that although Na and K are known to segregate to grain boundaries (GBs) in polycrystalline CIGSe thin films, no indications can be found that these alkali metals exhibit any passivating effect on GBs.